Teachers’ Roles in Remote English Teaching at SMA N 1 Payangan and The Challenges Encountered by English Teacher in Playing Their Roles - Leony, Ni Komang Via (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to determine the role played by the teacher in the context of distance learning at SMA N 1 Payangan. The results in this study, primarily observational data and also interview guides were taken. In this study, 2 English teachers at SMA N 1 Payangan were examined, namely Mrs Alice and Mr Hansen. The roles played by the two English teachers at SMA N 1 Payangan are based on the theory from Harmer (2001), in this theory, there are eight teacher roles played during the distance learning process. The role of the teacher includes Assessor, Organizer, Resource, Prompter, Controller, Participant, Tutor, and Observer. This study also examines the role of the academic language function used by the two English teachers at this school, in line with the theory of Hughes (1990) which has four elements of academic language that support the role played by the teacher in distance learning. Then finally in this study the researchers also found several challenges English teachers had to face during the distance learning process. This distance learning is carried out using the Zoom Meeting platform and also Google Meeting, and not only that the learning process is also carried out using the LMS and using the WhatsApp group.